The Introduction of Mapping Cultures in European Archaeology - Time Meets Space - Bandović, Aleksandar (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2017)
Prehistoric archaeology derives its roots from various practices and sciences: antiquarianism, natural history, geology, philology etc. The key conceptual tools of archaeology, including its “basic bloc” – archaeological culture, were formed by the end of the 19th century. Identifying the spatial dimension of archaeological cultures is largely linked to the innovations in adjacent disciplines, such as anthropogeography and its founder Friedrich Ratzel, but also with the general developments in cartography, perceived as a useful and “objective” tool for mapping the European nation states and various ethnic and linguistic communities. Ratzel based his ideas upon the ones of Moritz Wagner, geographer, traveller and researcher, and his work Law of the Migration of Organisms, conceived as an extension to Darwin’s theory of evolution. The innovative method of mapping cultures, as well as migrationism, have both remained permanent traits of Ratzel’s anthropogeography and the school of “cultural circles”. The examples from German-speaking archaeology demonstrate beyond doubt the ways in which the visualisation of archaeological cultures influenced the interpretations of European prehistory.